Effects of exercise on bone metabolism in postmenopausal women: a systematic review and meta-analysis of randomized controlled trials - Zhang, Wenhua; Li, Xun; He, Qiang; Wang, Xiaoqiang (Frontiers in Endocrinology, 2025)
ObjectiveTo assess the impact of exercise on bone metabolism in postmenopausal women through meta-analysis, and to offer evidence-based guidance for preventing and managing osteoporosis in this population.MethodsWe searched PubMed, Embase, and other databases using keywords such as “exercise,” “postmenopausal women,” and “bone metabolism” to identify randomized controlled trials published up to 2024 on the effect of exercise on bone metabolism in postmenopausal women. Studies were selected according to predefined inclusion and exclusion criteria. Data were analyzed using Review Manager 5.4 and Stata17. Study quality was assessed with the Cochrane risk-of-bias tool. Effect sizes were pooled as standardized mean differences(SMDs)with 95% confidence intervals(CIs), and heterogeneity was evaluated with the I²statistic. A fixed-effects model was used when I²≤50%; otherwise, a random-effects model was applied. The overall evidence certainty was rated using the Grading of recommendations assessment, development, and evaluation(GRADE)system.ResultsA meta-analysis of 24 studies(1067 subjects total)showed that exercise significantly elevated the levels of alkaline phosphatase(ALP)(SMD = 0.49, 95%CI: 0.21-0.77, P = 0.0006), N-terminal propeptide of type I procollagen(P1NP)(SMD = 0.62, 95% CI: 0.24 to 1.01, P = 0.002)and osteocalcin(OC)(SMD = 0.21, 95% CI: 0.05 to 0.37, P = 0.01); exercise significantly reduced the levels of parathyroid hormone(PTH)(SMD=-0.51, 95% CI: -0.77 to -0.25, P = 0.0001)and type I collagen cross-linked C-terminal peptide(CTX)(SMD=-0.32, 95% CI: -0.51to-0.12, P = 0.001). Subgroup analyses showed that aerobic exercise(SMD=-0.35, 95% CI: -0.65 to -0.06, P = 0.02) significantly reduced CTX levels, while both aerobic exercise(SMD = 0.23, 95% CI: 0.01 to 0.44, P = 0.04)and resistance exercise(SMD = 0.65, 95% CI: 0.10 to 1.20, P = 0.02)significantly increased OC levels. Exercise interventions lasting ≤6 months(SMD=-0.45, 95% CI: -0.72 to -0.18, P = 0.001)and sessions of ≤60 min(SMD=-0.48, 95% CI: -0.80 to -0.17, P = 0.003)both significantly reduced CTX levels, exercise interventions lasting ≤6 months(SMD = 0.35, 95% CI: 0.13 to 0.57, P = 0.002)and sessions of ≤60 min(SMD = 0.20, 95% CI: 0.01 to 0.39, P = 0.04)can significantly both increase OC levels.ConclusionExercise significantly improves bone metabolism in postmenopausal women by reducing bone resorption and promoting bone formation. Aerobic exercise lowers CTX levels, while both aerobic and resistance exercise increase OC levels. Short-term (≤6 months) and moderate-length (≤60 minutes/session) interventions are particularly effective. However, more high-quality randomized controlled trials are needed to confirm these benefits.Systematic review registrationhttps://www.crd.york.ac.uk/, identifier CRD42024610810.